Peran Pola Asuh Orang Tua terhadap Pemilihan Karir - Firda Lulu Chafidoh; Wiwik Kusdaryani; Desi Maulia (Universitas Muhammadiyah Metro, 2025)
The finding that there is still a career choice related to parental parenting patterns is the basis of this research. The purpose of this research is to find the relationship between the role of parental parenting patterns on the career choices of class XII students of SMK Negeri 1 Semarang. In this research, the method used is quantitative with the type of correlational research, the population in this study was 558. The sample of this research was 120 students who were determined by random sampling technique. The data collection technique used a self-control scale and an academic procrastination scale. Based on the results of the hypothesis of this research is